Effect of season on oocyte maturation and embryo development in buffalo - BAG, SADHAN; MEHRE, P V; MAJUMDAR, A C (The Indian Journal of Animal Sciences, 2010)
An attempt was made to find out the effect of season on oocyte maturation and embryo development in buffalo during low breeding season when environmental temperature was high. Oocytes were isolated from oocytes brought from local slaughter house during different months, viz. March (group 1), April (group 2) and May (group 3), when the environmental temperature was high. Isolated oocytes during different months were matured in TCM-199 with 10% FBS supplemented with follicular fluid and FSH (0.5ug/ml). Matured oocytes were fertilized by co incubating capacitated frozen thawed buffalo semen. After co incubation the oocytes were cultured in mSOF and cleavage rate and embryo development were noted. A total number of 1 340 buffalo ovaries were collected from local slaughterhouse, from which 1 080 culturable cumulus oocytes complexes (COCs) were recovered. The overall recovery rate of buffalo oocytes was 0.85 oocyte/ovary in the present study. The maturation rate of oocytes was 68.00 to 87.57%. The cleavage rate as well as morula stage embryo development in March (group 2), April (group 2) and May (group 3) were of 8.27 and 2.5, 5.6 and 3.1, 8.18 and 5.4% respectively. The average cleavage rate and morula stage embryo development were 9.60% and 4.60%.